Readjusting the social democratic welfare state in Denmark 1973 - 2003 - Claudia Bogedan (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2006)
As a social democratic welfare state, Denmark has offered universal and generous benefits promoting equality and diminishing stigmatisation; provision is almost entirely taxfinanced and public services play an important role. Consequently, welfare state spending has been traditionally high. Thus, one would expect that globalisation and low economic growth will threaten this welfare state arrangement. However, the example of Denmark shows that high public expenditure on the welfare state could be conserved. Albeit, in the last decade this small country in the North of Europe has gained much attention as role model for successful welfare state restructuring. The question is thus, how did Denmark readjust its welfare state to the changed environment? Therefore the present paper focuses on policy developments in four major welfare programmes: health care, labour market, old-age pensions and family since the 1970s. By comparatively contrasting these developments the paper is furthermore able to identify patterns in the process of readjusting the Danish welfare state.
Keywords: 300; Sozialreform; Dänemark